Perbaikan kualitas semai tusam pasca sapih melalui aplikasi trichoderma formulasi, pupuk lambat tersedia dan substitusi media tumbuh: Quality improvement of transplanted pine seedling by application of formulated trichod - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The experiment was conducted based on damage developed on pine nursery, which killed pine seedlings at a significant number. The damage started on 4 month-aged seedlings indicated by yellowing of needle, followed by development of brown spots on the needle and subsequently could kill the transplanted seedlings. Application of formulated Trichoderma and slow released fertilizer was aimed to avoid the initial symptom, which was assumed due to nutrient deficiency and to control the subsequent infection and disease development. Substitution of composting materials and rice hull into regular growth medium as the main treatment resulted 4 combination treatments. The results indicated that despite all treatments showed significant effects, application of Trichoderma together with slow released fertilizer (P1T1) on regular medium (medium IV) gave the highest growth increment peifortnance and suppression of damage in seedlings. Keywords: pine seedling, slow-released fertilizer, Trichoderma MITISARI Penelitian ini dilakukan karena adanya kerusakan di persemaian tusam yang mengakibatkan semai mati dalam jumlah besar. Kerusakan dimulai saat semai berumur 4 bulan dengan gejala kuningua daun Sarum yang berkembang menjadi bercak coklat, diikuti dengan kematian semai. Pembenan pelet Trichoderma dan pupuk lambat tersedia selain dimaksudkan untuk mencegah munculnya gejala yang diduga karena kekuranaan hara, juga untuk mengendalikan patogen yang muncul dan perkembangan penyakit. Substitusi kompos dan sekam ke dalam media tumbuh sebagai perlakuan utama menghasilkan 4 kombinasi perlakuan. Hasil penelitian menunjukkan bah wa semua perlakuan menunjukkan hasil yang signifikan, pemberian Trichoderma bersamaan dengan pupuk Ipmbat (P1T1) dalam media yang digunakan (media IV) menunjukkan menghasilkan semai paling Unggi dan mengurangi-kerusakan semai. Kara kunci: pupuk lambat, semai tusam, Trichoderma